Time-bound Hierarchical Key Assignment: An Overview - ZHU, Wen Tao (Institutional Knowledge at Singapore Management University, 2010)
The access privileges in distributed systems can be effectively organized as a partial-order hierarchy that consists of distinct security classes, and the access rights are often designated with certain temporal restrictions. The time-bound hierarchical key assignment problem is to assign distinct cryptographic keys to distinct security classes according to their privileges so that users from a higher class can use their class key to derive the keys of lower classes, and these keys are time-variant with respect to sequentially allocated temporal units called time slots. In this paper, we present the involved principle, survey the state of the art, and particularly, look into two representative approaches to time-bound hierarchical key assignment for in-depth case studies.